1972
DOI: 10.1080/00288233.1972.10421627
|View full text |Cite
|
Sign up to set email alerts
|

The effect of formaldehyde treatment on the chemical composition and nutritive value of silage

Abstract: Two experiments were conducted in which solutions of formaldehyde (HCHO) were applied to clover-dominant herbage before conservation as high-moisture silage.In Experiment 1 the HCHO application rates were 0, 0.6, 1.1. 2.2, and 4.4% (wjw of the dry matter treated), and 15 kg quantities of the herbage were ensiled in small polythene containers. Rates of HCHO up to 2.2% decreased the content of acetic acid, increased the content of a compound identified as 2,3~butanediol, but had no effect on silage pH (4.74 unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

1973
1973
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 17 publications
1
7
1
1
Order By: Relevance
“…In contrast to the findings of Barry and his colleagues (2), in this experiment methionine infusions had no effect on food intake. The supplementation technique used by Barry et al was to give D-L-methionine as an intraperitoneal injection while here L-methionine was administered as an intravenous infusion, but this difference seems unlikely to explain the disagreement between the results.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In contrast to the findings of Barry and his colleagues (2), in this experiment methionine infusions had no effect on food intake. The supplementation technique used by Barry et al was to give D-L-methionine as an intraperitoneal injection while here L-methionine was administered as an intravenous infusion, but this difference seems unlikely to explain the disagreement between the results.…”
Section: Discussioncontrasting
confidence: 78%
“…Barry, Fennessy and Duncan (2) reported that in sheep given a red clover/grass silage ad lib., intake was increased by 30% by intraperitoneal injections of D-L-methionine. This indicates that with some silages there is an imbalance in the supply of amino acids to the tissues which can affect appetite, possibly in a way analagous to that observed in monogastric animals (9).…”
Section: Introductionmentioning
confidence: 98%
“…The problem of achieving a decisive result is complicated by the marked effect on silage properties of the level of application of additive and of the composition of the mixture when one is used (Barry & Fennessy 1972;Davidson & Stevenson 1973;Wilson & Wilkins 1973;Wilkins et al 1974) .…”
Section: Discussionmentioning
confidence: 97%
“…While work progressed on formic acid as an additive for lucerne silage (Lancaster et ale 1977) the possible improvements to silage quality of adding formaldehyde were becoming apparent (Wilson & Wilkins 1970;Barry & Fennessy 1972) . During the experiments of Lancaster et ale (1977) a silage made with a mixture of formalin and formic acid was compared with one made with formic acid alone, and with untreated silage.…”
Section: Introductionmentioning
confidence: 98%
“…The chemical characteristics of silage can be altered by wilting (Castle & Watson 1970;Jackson & Forbes 1970;Donaldson & Edwards 1976;Hinks et al 1976) and by the addition of formalin (Barry & Fennessy 1972;Brown & Valentine 1972;Valentine & Brown 1973;Valentine & Radcliffe 1975). However, it is not lmown whether milk yield and composition can be influenced by these changes, as previous studies (Brown 1960;Murdoch 1962;Kormos 1967;Castle & Watson 1970;Fisher et al 1971; Valentine & Radcliffe 1975) have included confounding effects due to different levels of feeding, and the supplementation of silages with concentrates.…”
Section: Introductionmentioning
confidence: 99%